UPAYA GURU MENINGKATKAN SOFT SKILL PESERTA DIDIK - Hika Safitri; Nadiah Nadiah (Tarbiyatuna Kajian Pendidikan Islam, 2024)
The background of this research looks at the psychological condition of class XI students at SMAS BINA PANGUDI LUHUR which is caused by external and internal conditions of adolescents experiencing unstable emotional turmoil, so to control themselves they face problems in practicing the rules of religious teachings in everyday life. The teacher's role and duties must provide change, seek to answer educational challenges through observation to carry out evaluations, in the form of developing Intellectual, Emotional, and Moral aspects. This study uses a descriptive qualitative approach. Source of data obtained from primary data and secondary data. The results of the study show that the teacher's efforts to improve students' soft skills can take place in learning, such as giving good examples of speaking using the lecture method, getting used to reading books for 15 minutes, then solving problems through group discussions in the form of answering questions and giving good answers. , and enable students to participate in learning activities.